Turning Trash into Treasure: Unveiling Public Approval and Government Energy Policies in Thailand's Waste-to-Energy Evolution - Min, Li (Scholar: Human Sciences, 2025)
Purpose: Waste-to-energy development in Thailand has gained significant attention to seeks sustainable solutions to its waste management challenges. Hence, this research aims to examine the significant impact of trust in government, perceived risk, perceived benefits, place attachment, government energy policies, public acceptance on waste-to-energy development. Research design, data, and methodology: The researcher assessed 500 residents in Bangkok Perimeters in Thailand. Target population are residents, living in Nonthaburi, Nakhon Pathom, Pathum Thani, Samutprakarn and Samutsakorn who are over 24 years old and over. There are purposive sampling, stratified random sampling, convenience and snowball sampling. Before the data collection, Content validity was assessed by item-objective congruence (IOC), and reliability test was conducted by the pilot test (n=35), using Cronbach’s Alpha. After the data collection, the data analysis was applied through Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM). Results: The results show that trust in government, place attachment, and perceived benefits significantly impact perceived risk and public acceptance. Perceived risk strongly influences public acceptance, while government energy policies play a significant role in waste-to-energy development. Conclusions: The findings can contribute to the Thai government and public on the waste-to-energy development and related plans to accelerate the country’s waste management and energy consumption.